P THE ROLE OF INFLUENCERS IN THE SPREAD OF NEW VOCABULARY - Laeli Qadrianti; Muh. Syukri Gaffar; Nurrahma; A. Anna Fauziah; Putri Amalia; Al Mutazam (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
The purpose of this study is to examine the role of influencers in the dissemination of new vocabulary through social media. This research employs a qualitative research method involving social media content analysis and literature review. The study focuses on the mechanisms of new vocabulary dissemination and its impact on social communication and the development of the Indonesian language. The findings reveal that influencers utilize social media platforms such as Instagram, TikTok, and YouTube to create engaging and relevant content. Creative content in the form of short videos, memes, or interactive stories is often used to introduce new terms. Examples of vocabulary such as